Application of statistical methods in various disciplines - Aziz, Nazrina; Zain, Zakiyah (Universiti Utara Malaysia Press, 2019)
As Leonardo da Vinci once said, “Simplicity is the ultimate sophistication.” This book is evidence of how diverse problems can be solved using basic statistical methods; from the minute molecule level to widespread epidemic issues, data analysis can be accomplished using basic statistical methods with sound scientific thinking.This book is a valuable resource for students, academics and practitioners seeking simple yet effective solutions to real problems. The six chapters presented are indeed worthy additions to the literature, which will potentially enhance understanding of statistics and its applications. Statistics is a scientific way of unravelling the story behind the data – enjoy the story!